Comparison of psychotic bipolar disorder, schizoaffective disorder, and schizophrenia: an international, multisite study. (11th June 2015) - Tondo, L.; Vázquez, G. H.; Baethge, C.; Baronessa, C.; Bolzani, L.; Koukopoulos, A.; Mazzarini, L.; Murru, A.; Pacchiarotti, I.; Pinna, M.; Salvatore, P.; Sani, G.; et al.
Abstract : Objective: Nosological distinctions among schizoaffective disorder (SA), bipolar I disorder with psychotic features (BDp), and schizophrenia (SZ) remain unresolved. Method: We compared 2269 subjects with psychotic features in DSM‐IV‐TR diagnoses (1435 BDp, 463 SZ, 371 SA) from 8 collaborating international sites, by 12 sociodemographic and clinical measures, all between diagnostic pairs. Results: In bivariate comparisons, SA was consistently intermediate between BDp and SZ for 11/12 features (except onset stressors), and SZ vs. BDp differed in all 12 factors. SA differed from both BDp and SZ in 9/12 factors: SA and BDp were similar in education and suicidal ideation or acts; SA and SZ were similar in education, onset stressors, and substance abuse. Meta‐analytic comparisons of diagnostic pairs for 10 categorical factors indicated similar differences of SA from both SZ and BDp. Multivariate modeling indicated significantly independent differences between BDp and SZ (8 factors), SA vs. SZ (5), and BDp vs. SA (3). Measurement variance was similar for all diagnoses. Conclusion: SA was consistently intermediate between BDp and SZ. The three diagnostic groups ranked: BDp > SA > SZ related to lesser morbidity or disability. The findings are not consistent with a dyadic Kraepelinian categorization, although the considerable overlap among the three DSM‐IV diagnostic groups indicates uncertain boundaries if they represent distinct disorders.